Coordinate suppression of B cell lymphoma by PTEN and SHIP phosphatases - Miletic, Ana V. (The Rockefeller University Press, 2010)
The inositol phosphatases phosphatase and tensin homologue (PTEN) and Src homology 2 domain–containing inositol phosphatase (SHIP) negatively regulate phosphatidylinositol-3-kinase (PI3K)–mediated growth, survival, and proliferation of hematopoietic cells. Although deletion of PTEN in mouse T cells results in lethal T cell lymphomas, we find that animals lacking PTEN or SHIP in B cells show no evidence of malignancy. However, concomitant deletion of PTEN and SHIP (bPTEN/SHIP(−/−)) results in spontaneous and lethal mature B cell neoplasms consistent with marginal zone lymphoma or, less frequently, follicular or centroblastic lymphoma. bPTEN/SHIP(−/−) B cells exhibit enhanced survival and express more MCL1 and less Bim. These cells also express low amounts of p27(kip1) and high amounts of cyclin D3 and thus appear poised to undergo proliferative expansion. Unlike normal B cells, bPTEN/SHIP(−/−) B cells proliferate to the prosurvival factor B cell activating factor (BAFF). Interestingly, although BAFF availability may promote lymphoma progression, we demonstrate that BAFF is not required for the expansion of transferred bPTEN/SHIP(−/−) B cells. This study reveals that PTEN and SHIP act cooperatively to suppress B cell lymphoma and provides the first direct evidence that SHIP is a tumor suppressor. As such, assessment of both PTEN and SHIP function are relevant to understanding the etiology of human B cell malignancies that exhibit augmented activation of the PI3K pathway.